Body image and visual impairments: a bibliographic review of relationships between blindness and the development of body image - DOI: 10.4025/actascihumansoc.v30i2.1936 - Alves, Maria Luíza Tanure (2008)
The main goal of this study was to put together important information about body image development in blind people to help physical education teachers who work with this population. In order to achieve this goal, we conducted a search for articles published between 1990 and 2004. We analyzed and interpreted the most important aspects of each paper. Blindness is responsible for a poor and confusing body image, which is formed mainly by tactile, kinesthetic and audible information. Blind children tend to present self-concept and self-esteem levels related to those they believe their parents’ are, and also related to the quality of their social life.